Macroscopic, Microscopic, and Phytochemical Screening Analysis of Medicinal Plants in Nagari Lasi, West Sumatra - Tika Afriani; Devahimer Harsep Rosi; Winda Mailinda (Biology, Medicine, & Natural Product Chemistry, 2025)
Indonesia is one of the countries titled “Megabiodiversity”, which has a high level of biodiversity, including medicinal plants. Medicinal plants utilize various parts of plants, such as roots, leaves, stems, and fruits for prevention, treatment, and pain relief. Nagari Lasi has great potential in the diversity of medicinal plants, but their utilization by the community is still limited due to a lack of knowledge. This study aims to identify the content of bioactive compounds in medicinal plants through macroscopic, microscopic, and phytochemical screening. The methods include organoleptic observation, macroscopic and microscopic analysis, and phytochemical tests. Of the 150 plant samples, the results showed that 78 samples contained alkaloids, 115 samples contained phenolics, 129 samples contained flavonoids, 75 samples contained steroids, 21 samples contained triterpenoids, and 119 samples contained saponins. This study provides basic information regarding the phytochemical content of medicinal plants in Nagari Lasi as a first step in developing traditional medicine.